Dissemination of an evidence-based treatment for cancer patients: training is the necessary first step - Brothers, Brittany M. (Transl Behav Med, 2014)
Evidence-based psychological treatments (EBTs) for cancer patients have not been disseminated in part due to lack of available training. The biobehavioral intervention (BBI) is an EBT designed to alleviate cancer stress and enhance coping. The current study evaluates a training program and uses the Theory of Planned Behavior (TpB) to analyze factors related to intentions to implement BBI. Mental health providers (n = 62) attended a training for BBI. Attendees’ supervisors (n = 40) were later surveyed. Repeated measure ANOVAs assessed change over time in knowledge gains, attitudes towards EBTs/BBI, and self-efficacy. Linear multiple regression analyses assessed relationships between these factors and implementation intentions. BBI knowledge and attitude scores increased from pre- to post-training (ps < 0.01). Significant predictors in the final model were BBI-specific attitudes and self-efficacy (ps < 0.05). The BBI training program was an effective dissemination vehicle. Intervention-specific attitudes and self-efficacy were key factors in predicting providers’ implementation intentions.